Validação concorrente das medidas de força de protração da escápula com dinamômetro hand-held em três diferentes populações - Liberatori Junior, Ricardo Marcos (2017)
Introduction: The shoulder joint is considered unstable due to poor bone congruence and due to being exposed to large ranges of motion. The scapular muscles provide a stable base for the humerus during movements at extreme amplitudes of arm elevation above the head. The scapular protractors are continually required during different activities of daily living and sports. Considering the biomechanical aspects of the protractors, some studies have reported different methods of evaluating their strength using the hand held dynamometer (HHD). Despite the HHD is an instrument that has demonstrated excellent reliability and validity for measures of muscular strength in the lower and upper limbs, there is a lack of studies that tested and found the validity of the HHD force measurements for the scapular protractors in relation to the dynamometer isokinetic considered gold standard for these measures. Objective: To perform a concurrent validity of the HHD scapular protraction measures at two different positions in three different populations. Methods: Sixty subjects of both sexes, divided into three groups, group glenoumeral instability (GI), swimmers group (SG) and healthy group (HG) participated in the study. All subjects were evaluated by the HHD in two positions, sitting and supine position, and by Biodex. Results: A moderate correlation was found between the HHD measurements in the sitting and supine positions in relation to Biodex for all individuals. There was a strong correlation between the measurements of HHD in sitting position and Biodex for all groups. Conclusion: The data suggest that the HHD is a valid instrument to measure the force of the protractors of the scapula in the sitting position, since these measures are closer to the measures of the Biodex and to provide better stability than the position lying in supine, independent of the shoulder condition.